A retrospective cohort study on the aetiology and characteristics of maxillofacial fractures presenting to a tertiary centre in the UK. (May 2022) - Abukhder, Munir; Mobarak, Dima
Abstract: Introduction: Approximately 3 million facial injuries occur annually, some of which result in maxillofacial fractures. The aim of our study was to evaluate the aetiology and characteristics of maxillofacial fractures presenting to the Queen Elizabeth Hospital in Birmingham. Methods: The medical records for 809 patients treated for maxillofacial fractures were retrospectively reviewed between the dates of 01/01/2016 to 30/06/2017. Results: A total of 1381 maxillofacial fractures were recorded. The majority of patients were males (n = 682, 84.3%) with a male:female ratio of 5.59:1. The age group with the highest number of admissions was the 26–50 years age group (n = 395, 48.8%). Assaults was found to be most frequent aetiological factor for maxillofacial fractures in the male cohort and falls was the leading cause of maxillofacial fractures in the female cohort. The most common fractured site in our study was the mandible (n = 599, 43.3%) with the angle and symphysis/parasymphysis regions of the mandible being the most susceptible to injury. Teams that were more frequently involved in the care of these patients included ophthalmology (n = 86) trauma and orthopaedics (n = 53), neurosurgery/neurology (n = 95) teams. Conclusion: Socioeconomic status plays a significant role in the aetiology of facial fractures. Furthermore, assaults and falls were found to be the leading aetiological factors for maxillofacial fractures in the male and female cohorts respectively. There is a need to develop strategies in preventing falls in care homes, and addressing violence in young people through public awareness campaigns via the public health sector to reduce the incidence of such fractures. Highlights: This study reported a male predominance in maxillofacial fractures, with the male:female ratio roughly 5.59:1.2. Roughly 79.23% of all maxillofacial fractures occurred between the ages of 16-50 years. The most common fractured site was the mandibular region, followed by the orbit, and the zygomatic region The most frequent aetiological factor was assault, followed by falls, and road traffic accidents. Patients that live in the most deprived 10% of small areas in England made up 32% of all admissions.